Peripheral administration of 11.7% hypertonic saline and phlebitis risk in acute ischemic stroke requiring hyperosmolar therapy in South Korea - Beom-Seok Seo; Hyesuk Hong; Jong Hwa Hong; Jisu Jung; Hyunsoo Kim (Acute and Critical Care, 2026)
Background: Hypertonic saline (HTS) is used for hyperosmolar therapy in acute ischemic stroke (AIS) but is traditionally administered via central venous catheter to minimize vascular complications. Procedural burden and urgency often necessitate peripheral administration in practice. We investigated phlebitis risk associated with peripheral 11.7% HTS in AIS patients requiring hyperosmolar therapy.Methods: This retrospective study included 200 AIS patients receiving hyperosmolar therapy with mannitol (January 2022–December 2024), classified into an HTS group (n=67) receiving additional peripheral 11.7% NaCl and a no-HTS group (n=133). Phlebitis was assessed using the Infusion Nurses Society Phlebitis Scale. The primary outcome was phlebitis within 72 hours of therapy initiation. Multivariable logistic regression assessed the independent association between HTS use and phlebitis, with a secondary analysis examining frequency-dependent risk.Results: Phlebitis occurred in 31.3% (21/67) of the HTS group versus 15.8% (21/133) of the no-HTS group (P=0.016). Among those with phlebitis, most cases were mild (grade 1, 90.5%; grade 2, 9.5%), with no grade 3 or higher events. HTS was independently associated with phlebitis (adjusted OR, 2.19; 95% CI, 1.02–4.70; P=0.044) but not with mortality or hospital length of stay. Single administration was not associated with increased risk, whereas two administrations (adjusted OR, 5.43; P=0.005) and three or more (adjusted OR, 3.59; P=0.016) were associated with markedly elevated risk (P for trend=0.002).Conclusions: Peripheral 11.7% HTS was associated with increased phlebitis risk, though cases were predominantly mild. Risk increased with repeated rather than single-dose administration, suggesting caution is warranted when multiple peripheral doses are required.